The Entrepreneurial Finance and the Issue of Funding Startup Companies - Achibane Mustapha; Jamal Tlaty (European Scientific Journal, ESJ, 2018)
The emergence of entrepreneurial finance as a research field is the result of a double interest from both entrepreneurship researchers and financiers. Indeed, researchers focus on the financial fact existing in all entrepreneurial projects, while financiers consider that entrepreneurial situations have specific features that we should lean on. Our article is a presentation of the basic mechanisms of the entrepreneurial Finance, and its relationship with the entrepreneurial venture in its early stages; it will also focus on the theoretical aspect on both the Agency theory and its developments, as well as on the emerging organization that takes into account the evolution of the Startups reality. Finally, we will make a presentation of the different modes of financing Startups. Our report reveals that little work was spent on funding the very beginnings of the entrepreneurial venture. To this end, the Finance business tends to stand out from the corporate finance by different concepts and new issues, including the notions of startup, TPE or ' gazelles', that are frequently used at the expense of the notion of firms or groups.